Achieving Girls’ Dreams to Become Leaders: A Case Study of ‘Girls Take Over’ Program in Indonesia - Mariza, Nazla (Jurnal Perempuan, 2020)
This paper emphasizes the importance of affirmative action to encourage women leadership, which is important to start from early age. Until now, women still face challenges in taking leadership position even to make decisions for themselves. From the age of children, the space for women has been limited due to patriarchal system which discriminates against women in almost every aspect of life including social, culture, politics, education and so on. This paper will specifically examines an example of affirmative action, namely Girls Take Over campaign, that aims to encourage girls’ leadership in Indonesia. The study analyses how GTO campaign in 2019 can increase girls’ leadership and agency among girls participants and how this campaign can also increase public support to empower girls. The analysis is based on secondary data from activity reports and empirical data from interviews with GTO 2019 participants including the girls and the leaders whose positions are taken over. The analysis is based on power relations theory, leadership theory, participation and safe space. The results of the analysis indicate that a GTO can increase the girls’ agency and power to fight for gender equality. They feel empowered, capable to lead and and safe to make decision. In addition, the campaign helpsopen the perspective of the leaders and their support to girls’ to speak up, lead and decide. This campaign shape opinion that safe space is important for girls to advance their leadership. It also forces the environment to accept the idea that women leadership is very important and it has to start from child-age.